PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP PENGELOLAAN ALOKASI DANA DESA (ADD) DALAM PENCAPAIAN GOOD GOVERNANCE PADA DESA MANULEA, KECAMATAN SASITAMEAN, KABUPATEN MALAKA - Christina Yunnita Garung; Linda Lomi Ga (Universitas Nusa Cendana, 2020)
The purpose of this study was to determine the effect of accountability and transparency on the management of village fund allocation and wanting good governance in Manulea Village, Sasitamean District, Malaka Regency. In this study, the type of research used by researchers is quantitative research using data. The population of this study was all village communities and village officials in Manulea. Based on the purposive sampling method, the number of samples obtained is 50 people. The data used by researchers are primary data and secondary data with data collection techniques using observations and questionnaires which are considered the main instruments. In the testing phase, researchers use several testing methods that are considered very important to use. The methods are: descriptive statistics, infrational statistics, classic assumption tests, hypothesis testing, and test coefficient of determination.Based on the results of the research that has been conducted, it is concluded that accountability and transparency are partially have a significant, affect on the management of village fund allocation. While accountability and transparency simultaneously have a significant effect on the management of village fund allocation in achieving good governance in Manulea Village, Sasitamean District, Malaka Regency. Keywords: Management of Village Fund Allocation, Accountability, Transparency